THE PUBLIC DEBT PHENOMENON IN FISCAL SUSTAINABILITY, AND FINANCIAL DEVIATIONS IN SELECTED OECD COUNTRIES - Özker, Ahmet Niyazi (International Journal of Research -GRANTHAALAYAH, 2022)
In this study, we attempt to put forth the sustainability phenomenon, an empirical that occurs a significant fiscal impact on developing countries, which aim to reach the desired economic growth levels. Sustainability of public fiscal balances, especially in terms of debt policies, refers to a structural impact mechanism that means paying debts without default and restructuring them without risk in a period when the payment and redemption deadlines have come, especially in terms of external debts. This mechanism of influence is also expressed in the restructuring of a financial process, which can be expressed in different values, especially in developing countries, and whether the defaulted public liabilities refer to the later debt phenomenon. In this respect, public fiscal sustainability means that the real level of future primary surpluses is equal to the current real value of the public debt at a fundamental level. In our analytical study, the four countries were taken as the basis and the analytical values of these four countries in the financial balances were determined as emerging economies on the basis of these selected countries as Turkey, Poland, Chile, and Mexico. Besides, based on debts and public deficits, this fact also means a sustainable fiscal structure that can emphasize all kinds of debt phenomena at different levels, especially local governments, and the central government throughout the country. In addition, a debt obligation covering the entire public sphere also expresses sustainability in the narrow sense, representing the central government budget, which is essential in terms of sustainable budget balances. On the other hand, the sustainability of debts in developing countries where foreign public debt is in question, especially the public debt of central banks, can also lead to unexpected financial weakness and vulnerabilities. The policies as public borrowing instruments can create uncertainty about the level of financial-institutional impact in terms of future principal and interest payments and negatively affect fiscal policies sustainability. In this context, the acceptability of this fiscal process regarding the receivables of all institutions such as private bondholders, banks, and the World Bank is accepted as the sustainability of the debts in an ongoing process with mutually positive financial formations. When countries demand debt from financial markets, they have to maintain their fiscal sustainability regarding whether they should retake financial risks, especially in developing countries. This approach, which can also be expressed as the stability of debts, also puts forward a position identical to the expectations of stable ground for developing economic growth potential and financial infrastructure.